Affibody-based targeting agent 131I-YZHER2: V2 for HER2-positive ovarian cancer xenografts - Hu, Hongyu; Hu, Xianwen; Li, Fangming; Wang, Guanlian; Cai, Jiong (Frontiers in Medicine, 2025)
BackgroundThe human epidermal growth factor receptor 2 (HER2) affibodies are multifunctional tools that, when labeled with radioactive isotopes, hold significant potential for the diagnosis and treatment of tumors exhibiting HER2 overexpression. This research focuses on the development of 131I-labeled HER2 affibodies as targeted radionuclide therapy agents (TRNT) for HER2-positive Ovarian carcinoma.MethodsThe YZHER2: V2 affibody targeting HER2 was synthesized through genetic recombination. It was labeled with 131I by the chloramine T method, and its radiochemical purity and stability were evaluated in vitro. The normal mice were subjected to a study on the pharmacokinetic characteristics of 131I-YZHER2: V2. An assessment was conducted on the uptake in tumors, biological distribution, and potential for therapeutic use of 131I-YZHER2: V2 using a HER2-positive SKOV-3 nude mouse model. The HER2-negative ID-8 mouse model was used as a negative control.Results131I-YZHER2: V2 was easily prepared, and the non-decayed corrected yield of 131I-YZHER2: V2 affibody molecular probe was 96.06% ± 1.26%, showing good stability within 6 h in both normal saline (NS) and fetal bovine serum (FBS). The affinity of 131I-YZHER2: V2 was 32.9 nmol/L by cell binding assay. Scintigraphy revealed rapid uptake of the tracer in HER2-positive tumors. The retention of radioactive metabolites in the stomach, kidney, and bladder indicates that radioactive metabolites are mainly excreted through the gastrointestinal tract and urinary system. No substantial radioactive accumulation was observed in the heart, liver, lungs, or muscle tissue. Notably, significant renal retention was also evident based on in vitro biological distribution analysis. Tumor accumulation, extended retention, and advantageous distribution were observed in mice with HER2-positive tumors. Mice treated with 131I-YZHER2: V2 showed reduced tumor growth and prolonged survival. In the negative control group, there was no obvious aggregation and inhibition of tumors, and radioactive uptake in the kidney and gastrointestinal tract was also observed.Conclusion131I-YZHER2: V2 has the potential to be explored as a new method for TRNT in HER2-positive ovarian cancer.